Anti-infammatory Effects of Co(II), Ni(II) and Cu(II) Complexes of Diclofenac Sodium - Kesharwani, Rachna; Singh, Pramila (Asian Journal of Chemistry, 2010)
Complexes of Co(ll), Ni(II) and Cu(II) with anti-inflammatory drug diclofenac sodium have been synthesized and evaluated for their anti-inflammatory activity by the carrageenan induced ratpaw edema test. A comparison of the compounds with Diclofenac sodium revealed that the Cu(II) and Co(ll) complexes were more effective than the drug itself.